Influence of ethical ideology and socio-demographic characteristics on turnover intention: A study of retail industry in India - Abhishek Shukla; Rajeev Srivastava (Cogent Business & Management, 2016)
Ascertaining the relationship between ethical ideology, socio-demographic characteristics and turnover intention appears to be a complex phenomenon. Through this study, an attempt has been made to investigate the relationship between ethical ideologies, individual differences and turnover intention. This study is based on ethical ideology model showing two dimensions (idealism and relativism) that plays an important role in ethical evaluation and behavior. The data were analyzed using descriptive statistics, Pearson correlations, and multiple regressions. Based on a survey of 564 employees of retail industry in India, ethical ideologies (e.g. idealism and relativism) are found to be negatively associated with turnover intention. Results of the relationship between demographic characteristics, ethical ideology and turnover intention have been found to be quiet interesting. The findings imply that ethical ideology and demographic characteristics will predict turnover intention in the organization.
Keywords: 650